If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = 17x + -36 Reorder the terms: 5x = -36 + 17x Solving 5x = -36 + 17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17x' to each side of the equation. 5x + -17x = -36 + 17x + -17x Combine like terms: 5x + -17x = -12x -12x = -36 + 17x + -17x Combine like terms: 17x + -17x = 0 -12x = -36 + 0 -12x = -36 Divide each side by '-12'. x = 3 Simplifying x = 3
| 4x-8x+15=55 | | 2x^3-6x^2-x-6=0 | | 6(42x+30)=-12(-25-4x) | | 3(-9+3)-5= | | -8=-v+5v | | 2(5x+4)-6m-2x= | | -5(m-3)+2m=27 | | 20+8(11q)=12 | | -78=7x-22 | | Y=4x^2-16x-52 | | 7y=210-15x | | 2(7a)-7=9 | | -32-5x=4(-8-3x) | | (x+0.75x)=600 | | 3+7k=122 | | 1831=4(x)+691 | | 276+2325-6656*n=235+6346*n | | -3m-9=24 | | 0.6x-0.3(3)=1.5 | | 2+5m=-2(2m-1) | | 0.18y+0.07(y+4000)=1780 | | -25-1/8p=3/8p | | 2(n-7)-(4-5n)=6n | | 240+42k=720+30k | | 2400x-2x^2=0 | | x-75=25 | | 2b+1/2=3 | | 29-79=-24 | | 23-(n-178)=35(n+76) | | 5r-6=3+8r | | 17-4*2.5=27 | | 5-(n-4)=3(n+89) |